The long-term use of psychiatric services within the Open Dialogue treatment system after first-episode psychosis. Issue 4 (2nd October 2017) - Bergström, Tomi; Alakare, Birgitta; Aaltonen, Jukka; Mäki, Pirjo; Köngäs-Saviaro, Päivi; Taskila, Jyri J.; Seikkula, Jaakko
Abstract: Open Dialogue is a family-oriented early intervention model for mental health problems developed in the health district of Western Lapland, Finland. In the present study, the aim was to describe how psychiatric services were used in Western Lapland after decades of first-episode psychosis services, and to analyze how baseline characteristics were related to re-admission rates and the total duration of psychiatric treatment in geographical area where Open Dialogue approaches were developed and efforts made to systematically apply them to all psychiatric treatments. The data were obtained from the medical histories of patients who had first-episode psychosis in 1992–2005 and who lived continuously within the catchment area during the observation years (1992–2015) ( N  = 65). From baseline up to 2015, average length of treatment was 6 ± 2 years, and significant decrease ( p  < .001) in total use of psychiatric services was observed. The admission rates and duration of treatment were highest with subjects who behaved aggressively ( U  = 270, p  < .005), and/or who were hospitalized ( U  = 157, p  < .001) and medicated ( U  = 114, p  < .001) at onset. Overall, external aggression at onset emerges as a factor that may challenge the application of the OD treatment principles, being associated with a greater need for hospitalization and longer treatment duration.